Analyzing Parts of Speech Mastery of Students of Grade 10 at SMA - Jenny Nur Idill Rohan Damanik; Yuni Enjelina Napitupulu; Titin Marpaung; Ingnatius Tumpal Hot Raja Silalahi; Dumaris E Silalahi (JURNAL PENDIDIKAN BAHASA, 2026)
Mastery of parts of speech is a fundamental aspect of English grammar that supports students’ ability to construct accurate and meaningful sentences. Despite its importance, many senior high school students still struggle to differentiate word functions and apply them correctly in writing, which creates a gap between the theoretical knowledge of grammar and its practical use in classroom learning. This study aims to analyze the mastery of the eight parts of speech—noun, pronoun, verb, adjective, adverb, preposition, conjunction, and interjection—among Grade 10 students of SMA Negeri 5 Pematangsiantar. The research employed a descriptive quantitative design with 35 students from class X-3 as participants, selected purposively because they had received basic grammar instruction. Data were collected through a 24-item essay test requiring students to identify and analyze words within sentences. The findings revealed that the overall mean score was 68.14, which falls into the Good category. The highest mastery was found in Adjectives (91.4), Prepositions (88.6), and Nouns (81.4), while the lowest mastery occurred in Verbs (50.0) and Adverbs (50.0). Furthermore, frequency distribution indicated that 42.86% of the students still performed poorly. These results suggest that while some students have strong mastery, many continue to face difficulties, particularly in functional categories such as verbs and adverbs. The study concludes that more contextual and practice-oriented teaching strategies are required to strengthen students’ grammar skills and overall English proficiency.